Team teaching work and its relationship with school management commitments in secondary education - Sucari, Wilson (2019)
The objective of this research was to determine the relationship between teaching team work and compliance with school management commitments at the Santa Rosa Secondary Educational Institution, 2018. The type of research that was used is the non-experimental one and the form was the descriptive and correlational, the research method is the hypothetico-deductive. The procedure for obtaining the data was through the application of two questionnaires in one to the teachers of the referred institution. The results indicate that there is a 0.8 correlation between the two variables, which implies a considerable positive relationship; From this, it is concluded that the teaching team work has a considerable influence on the fulfillment of the five commitments of school management emanated by the Ministry of Education of Peru.